Carbon cycling in the East Sea (Japan Sea): A review - Kim, Minkyoung; Hwang, Jeomshik; Kim, Guebuem; Na, Taehee; Kim, Tae-Hoon; Hyun, Jung-Ho (Frontiers in Marine Science, 2022)
The East Sea (also known as the Japan Sea; hereafter, EJS) is a semi-enclosed marginal sea surrounded by the Korean Peninsula, Russia, and the Japanese Islands. The EJS is connected to the Pacific through shallow straits. Thus, the EJS has its own thermohaline circulation and the characteristic biogeochemistry. The deep overturning circulation plays a critical role in carbon cycling including absorption of atmospheric CO2 and its sequestration into the interior of the sea. The turnover time of the deep EJS (>1000 m) is hundred years and probably varies depending on physical climate forcing. Thus, the effect of climate change on oceanic processes may be more easily detected in the EJS. In this paper, we summarize the current understanding of carbon cycling in the EJS. We focus especially on the Ulleung Basin in the southwestern EJS, from which more extensive data are available. Notable features of carbon cycling in the EJS include the following: primary productivity and the export/production ratio are higher than in the adjacent Pacific; the EJS is a net sink of atmospheric CO2 and anthropogenic CO2 content is 1% of the dissolved inorganic carbon inventory; dissolved inorganic carbon in the sea interior is mostly supplied by organic matter decomposition rather than CaCO3 dissolution and thus, the deep waters are vulnerable to acidification; N:P molar ratio of the deep waters is 13, lower than the Redfield ratio; concentration of dissolved organic carbon is significantly higher than in the oceans; and sediment resuspension and lateral transport is an important component of sinking particulate organic carbon (POC) flux. Another important feature is the temporal trends observed for the last few decades. For example, pH, calcium carbonate saturation status, and dissolved oxygen concentration in the sea interior have decreased, whereas dissolved inorganic carbon and likely, the inventory of anthropogenic CO2 have increased. These temporal trends have an implication on better understanding of the processes occurring more slowly in the oceans. Brief suggestions for future research that will improve our understanding of carbon cycling and its variability are provided at the end of the paper.